Maya cultural activism in Guatemala - Fischer, Edward F., 1966-; Brown, R. McKenna, 1954- (Critical reflections on Latin America series., 1996)
"An important collection of essays on Mayan activism. Included are pieces by native and non-native scholars reviewing Guatemalan history, ethnic violence, peasant and indigenous cultural resistance to the State, material culture, development, and literacy. Each article brings to the fore a concern for human rights"--Handbook of Latin American Studies, v. 57.